Rancangan Sistem Pembayaran Pada Toko Pempek Mama Tika Menggunakan Laravel Dengan Payment Gateaway Midtrans - Yulvianda, Renaldi; Muhammad Ismail (LPPM Universitas Dinamika Bangsa, 2024)
Mama Tika's Pempek Shop is one of the places that is busy with buyers, making the service busy, especially in the payment section. The problems found based on observations and interviews were that there were queues during the payment process at the cashier due to the recording of order notes, recording of sales results was still done in a ledger so it took quite a long time to record based on the type ordered, purchases still used menu leaflets and recorded in an order receipt by the waiter, errors during the payment transaction process can occur due to calculations using a calculator and this causes complaints from consumers if there is a discrepancy in the payment amount with what the consumer ordered, because there is no printed proof of the transaction (receipt) available. can be given to consumers and the supply of raw materials in making pempek is not controlled so that when the consumer orders one of the orders the raw materials are not available in the supply area (warehouse). The aim of this research is to produce a payment information system at the Mama Tika Pempek Shop using the Laravel framework with Midtrans payment gateway so that the subsequent payment system becomes easier, faster and more efficient. The research results obtained are that the system created can record payment transactions, sales, manage product stock and print reports related to sales data by the cashier. Owners can also access the system to monitor transaction processes and manage user data because the systems are integrated with each other. Each part of the system has been tested to ensure the success of the system in carrying out its functionality.